2020
DOI: 10.3390/ijms21239018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Colorectal Cancer Prevention by Aspirin—A Literature Review and Perspective on the Role of COX-Dependent and -Independent Pathways

Abstract: Aspirin, synthesized and marketed in 1897 by Bayer, is one of the most widely used drugs in the world. It has a well-recognized role in decreasing inflammation, pain and fever, and in the prevention of thrombotic cardiovascular diseases. Its anti-inflammatory and cardio-protective actions have been well studied and occur through inhibition of cyclooxygenases (COX). Interestingly, a vast amount of epidemiological, preclinical and clinical studies have revealed aspirin as a promising chemopreventive agent, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 106 publications
0
27
0
Order By: Relevance
“…Nevertheless, the main anticancer activity of NSAIDs is thought to be a suppression of prostaglandin E 2 synthesis via COX-2 inhibition, which causes a decrease in tumor cell proliferation, angiogenesis, and increases apoptosis [ 36 , 61 ]. Although many of the anticancer mechanisms of NSAIDs are defined as COX-dependent, several signal transduction pathways (e.g., including nuclear factor-kappa B, NF-κB) have been confirmed as COX-independent NSAID-induced effects [ 62 , 63 , 64 , 65 ]. The correlation between the COX expression and colorectal cancer, including prognostic factors and putative chemopreventive agents, has been widely studied worldwide and reviewed in the past [ 66 ].…”
Section: Reviewmentioning
confidence: 99%
“…Nevertheless, the main anticancer activity of NSAIDs is thought to be a suppression of prostaglandin E 2 synthesis via COX-2 inhibition, which causes a decrease in tumor cell proliferation, angiogenesis, and increases apoptosis [ 36 , 61 ]. Although many of the anticancer mechanisms of NSAIDs are defined as COX-dependent, several signal transduction pathways (e.g., including nuclear factor-kappa B, NF-κB) have been confirmed as COX-independent NSAID-induced effects [ 62 , 63 , 64 , 65 ]. The correlation between the COX expression and colorectal cancer, including prognostic factors and putative chemopreventive agents, has been widely studied worldwide and reviewed in the past [ 66 ].…”
Section: Reviewmentioning
confidence: 99%
“…These molecules have been studied in many cancer types, and their expression profile and localization pattern have been found to differ in normal and tumor tissue as well as in different types of carcinomas. The roles of these molecules in tumor progression and suppression have also been investigated by many groups 13 , 14 . The dysregulation of these molecules occurs during carcinogenesis via different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that the only diagnostic metabolic biomarker with a downregulated trend in CRC patients compared to healthy controls was 2,3-DHBA. As a metabolite of aspirin and salicylic acid, it has been shown to inhibit colon cancer cell growth [ 33 , 34 ]. A consensus has not been reached on the anticancer mechanisms of 2,3-DHBA.…”
Section: Discussionmentioning
confidence: 99%